PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI ALJABAR KELAS VII SMP: Development of Problem Based Learning (PBL) Mathematics Learning Video Media in 7th Grade Algebra Materials of Junior High School - Rohmatin, Devi; Agustiani, Riza; Zahra, Atika (Universitas Tadulako, 2023)
This study aims to produce Problem Based Learning (PBL) learning video media on algebra material that is valid, practical, and has a potential effect on student learning outcomes. The type of research used is Research and Development (R&D). Tessmer's development research method focused on two stages, namely the preliminary stage and the prototyping stage using a formative evaluation flow consisting of self evaluation, expert review, one-to-one, small group, and field test stages. Data collection techniques used are validation sheets, questionnaires, interviews, and tests. The subjects in this study were students of SMPN 13 Palembang class VII.10. The research results from the validation of media, material, and technical quality aspects show that Problem Based Learning (PBL) video media for mathematics learning in algebra material is declared valid. In the one-to-one stage, students who were used as research subjects gave very good responses to the media used. At the small group stage with practical categories. The potential effect is based on the results of the student post test at the field test stage with a percentage of 87%. Based on the results of the study it can be concluded that the video media for mathematics learning based on Problem Based Learning (PBL) on algebra material is stated to be valid, practical, and has a potential effect on student learning outcomes